Proceedings Fifth Working Conference on Reverse Engineering (Cat. No.98TB100261)
DOI: 10.1109/wcre.1998.723190
|View full text |Cite
|
Sign up to set email alerts
|

Scalable visualizations to support reverse engineering: a framework for evaluation

Abstract: degrees throughout the software development cycle as aids to comprehension, analysis, and measurement. This research focuses on the experimental evaluation and refinement of a set of scalable visualizations that show promise for improving the overall software process. The roles which visualizations may play during reverse engineering and maintenance are of particular interest. This research also investigates the manner in which software visualizations are used in practice by software professionals. Partners fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Appendix A illustrates the CSD for Java's major control structures, while a more complete discussion of the CSD is given in [14].…”
Section: The Control Structure Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix A illustrates the CSD for Java's major control structures, while a more complete discussion of the CSD is given in [14].…”
Section: The Control Structure Diagrammentioning
confidence: 99%
“…It is clear from experience and from reports in the literature that a relationship exists between the syntactic form of source code and the ability of programmers to construct useful mental abstractions from that source code [11], [14]. Source code that is well structured and visually appealing facilitates the comprehension process.…”
Section: The Control Structure Diagrammentioning
confidence: 99%
“…Research over the years has envisioned different aspects of source code, the code itself, data flow, and run-time behavior. SV has been applied in various areas like algorithm animation [20,34], software engineering, concurrent program execution [23], static and dynamic visualizations of object-oriented code [81,89], fault diagnostics [1,95], debugging [4], and requirements analysis [24], to name a few. An extensive compilation of research relating to these fields can be found in [28,58,108].…”
mentioning
confidence: 99%